Computing Characterizations of Drugs for Ion Channels and Receptors Using Markov Models - Tveito, Aslak (Lecture Notes in Computational Science and Engineering, 2016)
Computational Science and Engineering; Biomedicine general; Computer Imaging, Vision, Pattern Recognition and Graphics